Assessment of shallow aquifer vulnerability to fluoride contamination using modified AHP-DRASTICH model as a tool for effective groundwater management, a case study in Yuncheng Basin, China. (January 2022) - Wang, Wanzhou; Mwiathi, Njagi Felix; Li, Chengcheng; Luo, Wenting; Zhang, Xin; An, Yonghui; Zhang, Mengnan; Gong, Peili; Liu, Juanjuan; Gao, Xubo
Abstract: Vulnerability assessment is an effective tool for the precaution of groundwater quality to specific pollutants. Groundwater fluoride pollution is severe and universal in the world, however, the method of groundwater risk assessment to fluorine is never built. The objective of this study was to establish an effective method to assess the potential level of groundwater vulnerability to fluoride by a modification of the typical DRASTIC model. The hydrogeochemical (H) factor (pH and TDS) was designed as a complementary parameter in the DRASTICH model. The weights of the parameters were revised by Analytical Hierarchy Process (AHP) method. The built AHP-DRASTICH model was applied to evaluate the groundwater vulnerability to fluoride contamination in Yuncheng basin, northern China, where groundwater with high fluoride concentration occurred extensively. The assessment result indicates that about 40 percent of the area belonged to relatively high and high vulnerability zones, which mainly distributed at the central part of the basin with strong evaporation and longer water-rock interaction time. The AHP-DRASTICH model shows a stronger positive correlation between risk scores and F concentration, giving better vulnerability assessment to F pollution compared with DARSTIC and DRASTICH models. The AHP-DRASTICH model is reliable and useful for guiding government and policy maker to take effective actions protecting groundwater from specific pollution. Graphical abstract: Image 1 Highlights: Groundwater risk assessment to fluoride contamination was produced. Hydrogeochemical factor first timely considered in groundwater vulnerability assessment. DRASTICH model was built by introducing the Hydrogeochemistry factor (pH and TDS). AHP-DRASTICH model gave better result to groundwater fluoride contamination. Abstract : Capsule : Hydrogeochemical (H) factor (pH and TDS) was first timely introduced into groundwater vulnerability assessment to fluoride contamination.